A survey of helminths in freshwater animals from some areas in Chiang Mai - Saenphet S. (2014)
Thirteen freshwater animals consisting of 8 species of fish, 1 species of shrimps and crabs and 3 species of mollusks collected during September 2000 from 8 sites in 4 districts of Chiang Mai Province: Hang Dong, San Pa Tong, Chom Tong and Hot were investigated for helminthes. Two metacercariae were recovered from 4 species of fish with the prevalence of 80.32%; Metacercariae of Stellantchasmus falcatus were found in the body cavity and under the scales of Dermogenus pusillus (39.34%) and the metacercariae of Haplorchoides sp were found only under the scales of Mystacoleucus marginatus, Systomus orphoides and Rasbora paviei, (40.98%). Adult of Acanthocephala, Pallisentis sp also recovered from the intestine of Trichopsis vittatus (3.29%). Moreover, Pleurolophocercous cercaria and redia were found in mollusk (Lymnaea sp) with the prevalence of 45.65%.